PENGARUH MEDIA TANAM DAN KONSENTRASI POC TERHADAP TANAMAN SAWI CAISIM (Brassica juncea L.) - Dwilyana, Lisa; Hidayat, Ramdan; Nugrahani, Pangesti (Fakultas Pertanian, Universitas Janabadra, 2024)
Efforts to improve agricultural techniques by integrating fish cultivation and mustard (Brassica Juncea L.) in one system, especially in limited space, can provide multiple benefits. Determining the appropriate planting media and concentration of POC needs to be done in hydroponic cultivation with a vertiminaponic system. The research was carried out in March-July 2022 at the Urban Farming Field Laboratory, Faculty of Agriculture, UPN